The Effect of Adding Lindur Flour (Bruguiera gymnorrhiza) on Chemical Characteristic and Acceptability of Patin (Pangasius sp.) Basreng - Zhenilla Mustika Berliana; Dewi Masithah, Endang; Nirmala, Dwitha (Universitas Airlangga, 2024)
Fried fish balls (basreng) are a type of product modified through two processing processes, namely boiling and frying. Frying process can have an impact on health due to high oil absorption resulting in high fat content values. This can be overcome by providing low-fat ingredients, namely lindur fruit flour. Lindur fruit flour tends to have a high starch content, namely in the hydroxyl group. The presence of hydroxyl groups is able to bind the water content of the dough, thereby reducing water evaporation which can form product pores when frying. Binding water to the dough reduces excessive oil absorption in the product. This study was conducted to determine the effect of lindur flour (Bruguiera gymnorrhiza) on chemical characteristic and acceptability of patin (Pangasius sp.). The treatment used in this study was the addition of 0%, 5%, 10%, dan 15% lindur fruit flour in the fish basreng. The parameters in this study are proximate content test and organoleptic test. The results showed that the addition of lindur fruit flour (Bruguiera gymnorrhiza) made a significant difference in the resulting basreng products. Patin basreng was the addition of 5% lindur fruit flour (Bruguiera gymnorrhiza) is the best patin basreng by the nutrient content and dan is the most preferred treatment by the panelis. Patin basreng was the addition of 5% lindur fruit flour (Bruguiera gymnorrhiza) has nutritional component 44,91% water; 1,78% ash; 8,27% protein; 8,11% fat; and 36,92% carbohydrate.